Prostaglandin signaling regulates renal multiciliated cell specification and maturation - Marra, Amanda N. (Proc Natl Acad Sci U S A, 2019)
Multiciliated cells (MCCs) are specialized epithelia with apical bundles of motile cilia that direct fluid flow. MCC dysfunction is associated with human diseases of the respiratory, reproductive, and central nervous systems. Further, the appearance of renal MCCs has been cataloged in several kidney conditions, where their function is unknown. Despite their pivotal health importance, many aspects of MCC development remain poorly understood. Here, we utilized a chemical screen to identify molecules that affect MCC ontogeny in the zebrafish embryo kidney, and found prostaglandin signaling is essential both for renal MCC progenitor formation and terminal differentiation. Moreover, we show that prostaglandin activity is required downstream of the transcription factor ets variant 5a (etv5a) during MCC fate choice, where modulating prostaglandin E(2) (PGE(2)) levels rescued MCC number. The discovery that prostaglandin signaling mediates renal MCC development has broad implications for other tissues, and could provide insight into a multitude of pathological states.